Economic and strategic policies in indonesia-china cooperation: advancing foreign language education as a tool for cultural and economic diplomacy - Hidayadi, Taufik; Zuhdi, Muhammad Luthfi; Yasin, Huda Riyana (Jurnal Konseling dan Pendidikan, 2025)
Indonesia-China cooperation in the economic field continues to increase in volume. This happened after the normalization of relations between Indonesia and China in 1990, then continued after the 1998 reforms in Indonesia, further activating the interrelationship between Indonesia and China through the policies carried out by President Abdurrahman Wahid, namely: began to visit China and was then continued by the next president. provide greater benefits for Indonesia. In addition, cultural diplomacy initiated by President Abdurrahman Wahid was Indonesia is increasingly placing its trust in China to increase cooperation between the two countries to reach the Comprehensive Strategic Partnership agreement in 2013. country. One of them is public and cultural diplomacy which includes educational diplomacy, namely by adding curriculum and study programs for Mandarin education at universities in Indonesia. Mandarin is one of the official languages spoken by the United Nations, so the language is considered appropriate to be taught in universities in Indonesia. Mastery of Mandarin provides bigger opportunity in education diplomacy in that shape from student exchange between Indonesia and China, thereby accelerating the understanding of culture, economic progress and technology controlled by China. The existence of this Mandarin language curriculum is a strategic policy for Indonesia. The method in this research is qualitative with a case study approach. Results of this study is expected donate for strategic policies for Indonesia in connection with China.